The phonological and visual basis of developmental dyslexia in Brazilian Portuguese reading children - Germano, Giseli D.; Reilhac, Caroline; Capellini, Simone A.; Valdois, Sylviane (Frontiers in Psychology, 2014)
Evidence from opaque languages suggests that visual attention processing abilities in addition to phonological skills may act as cognitive underpinnings of developmental dyslexia. We explored the role of these two cognitive abilities on reading fluency in Brazilian Portuguese, a more transparent orthography than French or English. Sixty-six dyslexic and normal Brazilian Portuguese children participated. They were administered three tasks of phonological skills (phoneme identification, phoneme and syllable blending) and three visual tasks (a letter global report task and two non-verbal tasks of visual closure and visual constancy). Results show that Brazilian Portuguese dyslexic children are impaired not only in phonological processing but further in visual processing. The phonological and visual processing abilities significantly and independently contribute to reading fluency in the whole population. Last, different cognitively homogeneous subtypes can be identified in the Brazilian Portuguese dyslexic population. Two subsets of dyslexic children were identified as having a single cognitive disorder, phonological or visual; another group exhibited a double deficit and a few children showed no visual or phonological disorder. Thus the current findings extend previous data from more opaque orthographies as French and English, in showing the importance of investigating visual processing skills in addition to phonological skills in dyslexic children whatever their language orthography transparency.